Levantamento de informações e promoção de melhorias no sistema e-Proc/TJTO para o Nacom - Seraphin, Angelo Stacciarini (Universidade Federal do Tocantins, 2016)
The present paper aimed to adequate the work developed by the Judicial District Support Center of the State of Tocantins, NACOM, the new technologies that are being used by the States Judicial System due to the modernization of the Judicial Park, as a whole. The modernization was necessary to ease one of the Judicial System's greatest problem, the time spent in each process. So to guarantee fundamental principals like judicial access and the process reasonable length, the creation of normative that implement the use of technologies in the procedural system, and the acquisition of equipments and innovating technology, brought to the Judiciary of Tocantins a new reality, especially with the implantation of the system e-Proc/TJTO. From this analysis it was possible to propose, based on the necessities that where brought up by the centers own managers, modifications inside the system that allowed a systematic improvement in the workflow of the users of the system e-Proc/TJTO, that substantially modified how they worked in the system. The goal of these modifications is to refine and allow a gain of productivity of the workers of the center while they operate the system e- Proc/TJTO, further on allowing a better management of the center by their managers.